The modern approach of advanced botulinum toxin therapy: application of various dilutions, techniques and levels of administration - I. P. Aksenenko (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
One modern direction of botulinum toxin therapy in aesthetic medicine is its individualization by taking into account patients' specific characteristics. On the example of using incobotulinumtoxin A (botulinum toxin type A, BTA), this paper considers the possibility of using the entire range of its concentrations in creating a differentiated approach to correcting mimic wrinkles in different zones and muscular levels. This is expected to achieve the required level of individualization for an optimal aesthetic result. Aim. To assess and justify the efficacy of BTA (on the example of incobotulinumtoxin A) in various concentrations for correcting mimic wrinkles in different zones and muscular levels.